2021
DOI: 10.1088/1402-4896/ac03df
|View full text |Cite
|
Sign up to set email alerts
|

Tunable optical isolator using Graphene-photonic crystal-based hybrid system

Abstract: In this article, an optical isolator is designed and simulated based on a hybrid configuration of the photonic crystal (PhC) and graphene. The PhC membrane is a hexagonal lattice of air holes arranged in a nonlinear silicon substrate. To provide a nonreciprocal transmission (optical isolator), breaking the symmetry of the light propagation path (the forth and back routes) is an essential condition. Here, the asymmetrical round trip of the light propagation and the Kerr-nonlinear effect are employed to obtain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…When the data in the figure are examined, there is an observed improvement in harmony of the chemical potential for Antenna-1 and the reflection coefficient, while inconsistency is observed for Antenna-2 and Antenna-3, especially at 0.7 eV. It has been shown that the polarization and permeability of the antennas can be achieved without making any changes in the antenna dimensions or physical structure only by changing the voltage applied to the graphene layer, which changed the Fermi energy level [94][95][96][97]. Equation (1) shows that the conductivity of graphene can be adjusted Figure 10 shows the bandwidth performance of the antennas in terms of return loss along with the lower (𝑓 𝐿 ) and upper (𝑓 𝐻 ) frequencies, where the return loss curve exceeds −10 dB.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…When the data in the figure are examined, there is an observed improvement in harmony of the chemical potential for Antenna-1 and the reflection coefficient, while inconsistency is observed for Antenna-2 and Antenna-3, especially at 0.7 eV. It has been shown that the polarization and permeability of the antennas can be achieved without making any changes in the antenna dimensions or physical structure only by changing the voltage applied to the graphene layer, which changed the Fermi energy level [94][95][96][97]. Equation (1) shows that the conductivity of graphene can be adjusted Figure 10 shows the bandwidth performance of the antennas in terms of return loss along with the lower (𝑓 𝐿 ) and upper (𝑓 𝐻 ) frequencies, where the return loss curve exceeds −10 dB.…”
Section: Resultsmentioning
confidence: 98%
“…It has been shown that the polarization and permeability of the antennas can be achieved without making any changes in the antenna dimensions or physical structure only by changing the voltage applied to the graphene layer, which changed the Fermi energy level [94][95][96][97]. Equation (1) shows that the conductivity of graphene can be adjusted dynamically by changing its chemical potential.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, 1D PCs can be easily fabricated by the chemical vapor deposition (CVD) technique [23]. A novel type of PCs is composed of sequential stacks of alternating graphene and dielectric layers which are well-known as one-dimensional graphene photonic crystals (1D GPCs) and have been utilized in many applications such as isolators [24], biosensors [25], modulators [26], faraday rotators [27], and temperature sensors [28]. On the other hand, anisotropy, which is an interesting feature of graphene, results in remarkable optical properties for GPCs [29]- [31].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a couple of research groups have utilized 2D materials for designing various electro-optic devices recently. Graphene having superior advantages [5,23], has emerged as a promising 2D material in designing THz photonic devices. Nowadays, there is a tendency to integrate multi-functional photonic devices on a single chip, having the advantages of compact size, high performance, low loss, and low power consumption [24].…”
Section: Introductionmentioning
confidence: 99%